Wilhelm Dilthey: Subject and History - Juozaitis, Arvydas (Problemos, 1986)
W. Dilthey’s approach towards cognition was a novelty in the background of traditional rationalism: it eliminated the relation subject-object. In the resulting “psychological” and “hermeneutical” investigations it became possible to treat consciousness and history (culture) as the medium of individual existence. However, the essential character of the medium in its turn was explicable only in terms of individual existence.